Hope, joy, and affection in the classical world - Caston, Ruth R. (Emotions of the past, 2016)
Scholarship on the emotions in classical antiquity has focused almost entirely on negative emotions, but that is not because the Greeks and Romans had little to say about positive emotions. The chapters in this collection show that there are representations of positive emotions - considered here under the headings of 'hope', 'joy', and 'affection' - extending from archaic Greek poetry, through the philosophical schools of the Epicureans and Stoics, to the Christianity of Augustine, and while many of the literary representations give expression to positive emotion but also describe its loss, the philosophers offer a more optimistic assessment of the possibilities of attaining joy or contentment in this life